JUNIOR HIGH SCHOOL MATHEMATICS TEACHERS’ PROFESSIONAL AND PERSONAL CHARACTERISTICS - ABELLAR, ELISA (Advances in Social Sciences Research Journal, 2021)
ABSTRACT This study sought to determine the Junior High School Mathematics teachers’ level of professional and personal characteristics in Maguindanao Division I. Specifically, it determined the Junior High School Mathematics Teachers’ level of Professional and personal characteristics; the Junior High School Students’ level of academic performance in Mathematics; and the significant relationships of the teachers’ level of Professional and personal characteristics and their Junior High students’ level of performance in Mathematics. The study used the descriptive-correlational survey method. It determined the level of teaching practices of twelve (12) Junior High School Mathematics teachers of Maguindanao Division I in terms of professional and personal characteristics. Pearson’s Product - Moment Correlation Coefficient was used to determine the significant relationship of the level of professional and personal characteristics of the junior high Mathematics teachers to the students’ level of academic performance. Based on the findings of the study, it is concluded that Junior High School Mathematics teachers’ professional and personal characteristics is very satisfactory. It is further concluded that the outstanding professional and personal characteristics of the teachers have no bearing on the academic achievement of the students. The students must work hard to get higher grades and the teacher must develop professional and personal characteristics to perform tasks exceedingly. Keywords: Professional and Personal Characteristics, Junior High School Mathematics Teachers, Level of Academic Performance